Ontologi Pendidikan Islam: Studi Kasus Pengajaran Nilai Islam di Jenjang Tsanawiyah Pesantren Imam Bukhari Karanganyar - Mujiburrohman, Mujiburrohman; Shodiq, Arsyad (TSAQOFAH, 2026)
Pesantren are the oldest Islamic educational institutions in Indonesia and, in their development, have been shaped by educational dynamics and societal needs, leading many pesantren to provide formal school education and various other activities to enhance the community’s economic potential with the pesantren as the central hub. The operation of pesantren is consistently grounded in an educational philosophy that serves as the basis for formulating educational goals, curricula, and educational practices. This study aimed to describe the educational philosophy at Pondok Pesantren Imam Bukhari Karanganyar. The research employed a field study model at a pesantren khalaf using a qualitative approach, in which data were obtained through interviews, direct observations at Pondok Pesantren Imam Bukhari Karanganyar, and document study. The collected data were then processed and qualitatively analyzed to uncover the philosophical dimensions that underlie educational practices at the pesantren. The findings show that there is an ontological foundation of educational philosophy at Pondok Pesantren Imam Bukhari Karanganyar that underpins the organization of educational processes and the development of the pesantren’s role within the wider community. These findings affirm the importance of Islamic educational philosophy studies as a normative and conceptual reference for the management of pesantren in an era of dynamic social change.